Tropidomyrmex elianae, a new myrmicine ant genus and species from Brazil, tentatively assigned to Solenopsidini (Hymenoptera, Formicidae) - Silva, Rogério R.; Feitosa, Rodrigo M.; Brandão, Carlos Roberto F.; Diniz, Jorge L. M. (Zootaxa, 2009)
A new myrmicine ant, Tropidomyrmex elianae gen. n. & sp. n., is described from southeastern and central Brazil, based on workers, ergatoid gynes, males and larvae. Tropidomyrmex workers are relatively small, monomorphic, characterized mainly by the feebly pigmented and extremely thin integument; subfalcate mandibles bearing a single apical tooth; palpal formula 1,2; clypeus relatively broad and convex; reduced compound eyes; propodeum unarmed and with a strongly medially depressed declivous face; double and bilobed well developed subpostpetiolar processes; and peculiarities in the sting apparatus. A colony fragment of T. elianae containing workers, ergatoid gynes, males, and brood was found inside a ground termite nest (Anoplotermes pacificus Apicotermitinae) in a montane rocky scrubland in the state of Minas Gerais, southeastern Brazil. Tropidomyrmex elianae is known also from two workers collected in leaf litter samples processed with a Winkler extractor, from the state of Tocantins, central-north Brazil. Despite the differences from the accepted solenopsidine genera, Tropidomyrmex is tentatively assigned to this tribe. Within the solenopsidine ants, the genus is apparently related to Tranopelta. Tropidomyrmex is marked by extreme reductions, perhaps reflecting adaptations to particular habits and habitats.